Reviewing the Transformation of Enterprise Systems in Indonesia through Integrated Design and Operations Management - Emor, Dewi Dian; Lumbantoruan, Cryzelda Minerva; Limpele, Briana; Lule, Benny; Nuphanudin, Nuphanudin (Journal of Social Work and Science Education, 2025)
This literature review aims to examine the transformation of enterprise systems in Indonesia through the integrated approach of design and operations management. The study investigates how enterprises in Indonesia are leveraging integrated design and operations management to enhance efficiency, quality, productivity, and competitive advantage in a rapidly evolving market. This study employs a Systematic Literature Review (SLR) methodology to conduct an in-depth analysis of academic journal articles pertaining to topics. The review encompasses articles published and indexed in Scopus databases from 2019 to 2025. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method is employed as the framework in this study. Through meticulous screening, data extraction, and synthesis of findings, this study aims to provide comprehensive insight into integrated design and operations management. However, the study also discusses the positive outcomes of successful integration, including improved decision-making and enhanced organizational flexibility. This study presents a novel approach by focusing specifically on Indonesian enterprises and their unique context, offering a deeper understanding of how integrated design and operations management. The contribution of this research lies in providing actionable insights for practitioners and policymakers in Indonesia to refine their strategies for implementing integrated enterprise systems. By synthesizing various perspectives, the study contributes to both academic knowledge and practical applications in the field of enterprise system transformation in the Indonesian context.